2019
DOI: 10.1177/2040622319891539
|View full text |Cite
|
Sign up to set email alerts
|

Serum adenosine deaminase activity and coronary artery disease: a retrospective case-control study based on 9929 participants

Abstract: Background: Adenosine deaminase (ADA) regulates purine metabolism through the conversion of adenosine to uric acid (UA). Adenosine and UA are closely associated with cardiovascular events, but the correlation between serum ADA activity and coronary artery disease (CAD) has not been defined. Methods: We performed a hospital-based retrospective case-control study that included a total of 5212 patients with CAD and 4717 sex- and age-matched controls. The serum activity of ADA was determined by peroxidase assays i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…We found that various metabolites in the metabolic pathway are closely related to the risk of CAD. 37 Hcy is formed in the one-carbon metabolism pathway during the metabolism of methionine to cysteine, and can also be used to regenerate methionine by vitamin B12. 38 Other studies have shown that serum Hcy levels are significant in CAD patients and that it is an independent risk factor for the disease.…”
Section: Discussionmentioning
confidence: 99%
“…We found that various metabolites in the metabolic pathway are closely related to the risk of CAD. 37 Hcy is formed in the one-carbon metabolism pathway during the metabolism of methionine to cysteine, and can also be used to regenerate methionine by vitamin B12. 38 Other studies have shown that serum Hcy levels are significant in CAD patients and that it is an independent risk factor for the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation exerts an important role in the development and progression of various diabetic complications. ADA is highly expressed in lymphoid tissues and is essential for the proliferation and differentiation of T lymphocytes as well as the regulation of the maturation and function of monocytes and macrophages ( 23 ). The expression of ADA is significantly increased in tissues rich in macrophage in a rat model of fecal peritonitis ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…We recently focused on the relationship between one-carbon metabolism and CVD. We found that various metabolites in the metabolic pathway are closely related to the risk of CAD [28]. Hcy is formed in the onecarbon metabolism pathway during the metabolism of methionine to cysteine, and can also be used to regenerate methionine by vitamin B12 [29].…”
Section: Discussionmentioning
confidence: 99%